Virtual urgent care in an integrated value based healthcare system - Khang Nguyen; Dinh Nguyen; Sinjin Lee; Jin Chang; Yvonne Bach; Kien La; Ferdinand Justus; Tianyuan Shao; Caleb Wang; Mason Kellogg; Raquel Taylor; Alan Evans (npj Digital Medicine)
Abstract Virtual urgent care (VUC) is not well understood when delivered through an integrated value-based healthcare system. The Southern California Permanente Medical Group operates Get Care Now (GCN), a VUC program complementing its urgent care clinics (UCC). Quality and patient experience dimensions are included in this study, comparing GCN and UCC patients. Females and Hispanics/Latinos were predominant in both groups and proportions of patients with chronic conditions were nearly identical within the leading 30–49 age band. Wait times for GCN were 21.19 min lower than for UCC, and positive patient survey results align with GCN’s average Net Promoter Score of 87. 3-day return rates to the ED (2.53% GCN vs. 3.26% UCC) and to UCC (5.44% GCN vs. 2.42% UCC) were comparable between GCN and UCC utilizers. Findings demonstrate that 24/7 VUC sustainably supports meeting patient demand for urgent care services in an integrated value-based system.